PELATIHAN PENINGKATAN KEMAMPUAN BERBAHASA INDONESIA MELALUI STORY TELLING BAGI SISWA SD NEGERI 2 LUBUKNGIN - Sri Murti; Nyayu Masnon Arif (LP4MK STKIP PGRI Lubuklinggau, 2023)
The use of Indonesian Language is a concern, especially in it is implementation in society. Based on the results of observations made by the service team at SD Negeri 02 Lubukngin, Selangit District Musirawas, information was obtained that good and correct use of Indonesian was still very low among students. This is proven by the results of students' work, especially for their writing skills, there are still many errors in using correct spelling. This condition has an impact on students' literacy skills at SD N 2 Lubukngin. The problem faced by partners is the difficulty in teaching students the proper and correct use of Indonesian. The results of students' work, both written and oral, show students' limited understanding of correct spelling. Another problem is that schools have not received special attention from the government or community organizations in the field of language to provide special training and guidance on the importance of using Indonesian properly and correctly at SD N 2 Lubukngin. The method used includes four stages, namely the initial stage, training stage, mentoring stage, and evaluation stage. The conclusion obtained through this training activity is that there has been an increase in Indonesian language skills, especially understanding the importance of spelling in writing. The final assessment results showed that the participants' writing ability through (story telling) was at a percentage of 64%. So it can be concluded that Indonesian language skills training for students at SD Negeri 2 Lubukngin is quite effective in improving Indonesian language skills in the field of writing.